Biodegradable FeWOx nanoparticles for CT/MR imaging-guided synergistic photothermal, photodynamic, and chemodynamic therapy. Issue 5 (29th January 2021) - Cheng, Yaru; Lu, Huiting; Yang, Fan; Zhang, Yiyi; Dong, Haifeng
Abstract : Biodegradable FeWO x -PEG-RGD nanoparticles for ( T 2 / T 1 -weighted) MR/CT dual-modal imaging-guided PTT/PDT/CDT synergistic therapy. Abstract : The development of a simple and effective single constituent multifunctional nanotheranostic platform producing a multimodality diagnostic signal and curing effect is still a challenge. Herein, we synthesized simple and biodegradable FeWO x ternary oxide nanoparticles and modified their surface with RGD–PEG–NH2 (FeWO x –PEG–RGD NPs), whereby resulting NPs possessed a ( T 2 / T 1 ) switchable MRI/CT dual-modal imaging ability and synergistic photothermal therapy (PTT)/photodynamic therapy (PDT)/chemodynamic therapy (CDT) capacity. We showed that FeWO x –PEG–RGD NPs enabled tumor accumulation under a magnetic field drive and RGD-mediated tumor penetration and implemented PTT/PDT treatment under 980 nm laser irradiation. In an acidic tumor microenvironment (TME) with a high hydrogen peroxide (H2 O2 ) expression, NPs degraded to release Fe 3+ and Fe 2+, triggering a Fenton reaction to generate ˙OH for CDT. The released Fe 2+ led to T 2 / T 1 signal conversion for tracing cancer therapy, while the high X-ray attenuation coefficient of W also made it a good CT contrast agent for guided therapy. Thus, the structurally simple FeWO x –PEG–RGD was capable of mediating ( T 2 / T 1 -weighted) MR/CT two modal imaging-guided PTT/PDT/CDT synergic therapy with a high accuracy and superb anticancer efficiency. The simple, degradable, rapid-clearance, and multifunctional FeWO x –PEG–RGD NPs provide a novel, promising, and versatile nanotheranostic platform.